Experimental Investigation of the Lubricant Effect of Thixotropic Slurry on Pipe–Soil Interfacial Friction Characteristics - Zhiqiang Wang; Jinli Wang; Luqiang He; Xiaoqiang Gu (Buildings)
Based on the technical issues encountered during underground pipe jacking construction in the Jining area, a series of ring shear tests were conducted on silty clay below the groundwater level to investigate the interfacial friction characteristics under the lubrication of thixotropic slurry during construction. Seven different slurry formulations were prepared, and ring shear tests were conducted under varying normal stresses, shear rates, and shear displacements. The friction characteristics during the shearing process were analyzed, and the corresponding friction coefficients were determined. The experimental results indicate that shear stress increases with increasing normal stress, but it is not affected by shear rate and shear displacement. As normal stress increases, the friction coefficient also exhibits a slight rise, which may be due to the uneven distribution of the slurry under pressure. Among the seven formulations, Slurry 1 exhibited the best lubricating effect, which reduced the friction coefficient by 64.5%, while Slurry 0 had the poorest effect with a reduction of 42.6% in friction coefficient. Additionally, the excessive addition of bentonite in the slurry reduces its lubricating effect, and the content of fiber has a significant effect on the friction reduction degree by thixotropic slurry.